2005
DOI: 10.1007/s10237-005-0074-y
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear elastic-viscoplastic constitutive equations for aging facial tissues

Abstract: This paper reports on the initial stages of a project to simulate the nonlinear mechanical behavior of an aging human face. A cross-section of the facial structure is considered to consist of a multilayered composite of tissues with differing mechanical behavior. The constitutive properties of these tissues are incorporated into a finite element model of the three-dimensional facial geometry. Relatively short time (elastic-viscoplastic) behavior is governed by equations previously developed which are consisten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…Especially when discretizing the individual skin layers, it might become essential to model skin using membrane or shell elements to increase computational efficiency, to ensure well-conditioning of the overall system matrix, and to avoid the typical locking effects associated with thin geometries subjected to bending [59]. Fourth, the calibration of the material parameters for both the elastic model and the growth model remains a question to be addressed in the future [44]. Here, for conceptual comparison, we have only used generic material parameter values.…”
Section: Example Of Skin Expansion and Growthmentioning
confidence: 99%
“…Especially when discretizing the individual skin layers, it might become essential to model skin using membrane or shell elements to increase computational efficiency, to ensure well-conditioning of the overall system matrix, and to avoid the typical locking effects associated with thin geometries subjected to bending [59]. Fourth, the calibration of the material parameters for both the elastic model and the growth model remains a question to be addressed in the future [44]. Here, for conceptual comparison, we have only used generic material parameter values.…”
Section: Example Of Skin Expansion and Growthmentioning
confidence: 99%
“…We have recently shown that it is straightforward combine our growth model with in-plane anisotropy, introduced through pronounced stiffness along Langer’s lines [9, 30]. It might also be interesting to elaborate out-of-plane anisotropy and model the different skin layers individually [39]. We have demonstrated how to model the growth process itself as anisotropic as well [16].…”
Section: Discussionmentioning
confidence: 99%
“…The soft tissue model proposed by Rubin and Bodner [2002] provides a versatile framework [Helfenstein et al, 2010] to represent the mechanical behavior of collagenous tissues [Mazza et al, 2005;Barbarino et al, 2011;Weickenmeier and Jabareen, 2014;Flynn and Rubin, 2014;Safadi and Rubin, 2014] offering the possibility to include dissipative, inelastic characteristics. In application to FM tissues, Jabareen et al [2009] used an elastic isotropic formulation of the Rubin-Bodner (RB) model to represent the uniaxial response of the amnion.…”
Section: Introductionmentioning
confidence: 99%